IbM-Pelatihan Teknik Penulisan Parafrase Untuk Skripsi Mahasiswa Sebagai Upaya Menghindari Plagiarisme - Sahla, Widya Ais; Mukhlisah, Nurul; Julkawait, Julkawait; Irwansyah, Rusman (Jurnal IMPACT: Implementation and Action, 2019)
The issue of plagiarism is one of the issues that gets great attention among the academic world and is our common concern. As a manufacturer of science, Higher Education has a big responsibility to provide education and socialization related to the prevention of plagiarism. The initial conditions of our partners (students of the Islamic Economics Study Program, Faculty of Islamic Studies, Kalimantan Islamic University, Syeh Muhammad Arsyad Al-Banjari), are having difficulties in avoiding the culture of copy-paste in completing their academic assignments, especially in doing thesis. Most students still do not understand the term plagiarism and how to avoid it. After going through community service activities under the title "Training of Paraphrasing Techniques for Writing Student Thesis as an Effort to Avoid Plagiarism" which we carried out on September 22, 2018 then our partners can apply good paraphrasing techniques to avoid plagiarism.